Communication and information system for individual performance - Syahdan, Rinto (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
The research results so far are considered to ignore the relationship between the use of information systems and the satisfaction of using information systems. Moreover, on how user satisfaction information systems can â€œbridgeâ€ the relationship between the use of information systems and individual performance. This study was aimed at testing the effect of the use of information systems on the satisfaction of the use of information systems and test user satisfaction as mediation on the relationship between users of information systems and individual performance. The population in this study is most Civil Servants throughout North Maluku Province. The samples in this study were taken using purposive sampling with criteria is the operator of regional financial information systems in each regional device work unit in the Regional Government of North Maluku Province, Ternate City, and Tidore Islands City. The study used simple linear regression and hierarchy in hypothesis testing. The results showed that all hypotheses submitted were entirely supported in this study. Conclusions, suggestions, and recommendations of future research are also discussed at the end of this study.